For the technically minded... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
CD-ROM discs are like the compact discs bought in music stores :12 cm in diameter and 1.2 mm thick. The data is encoded in a shiny, metallic film in the form of tiny pits and lands which can be of different lengths but are of standard depth and...